Zero-sequence compensation method of line longitudinal current differential protection based on 5G distribution network - XU Rui; YU Yuexiang; LI Xiao; JIN Yechen; ZHAO Fang (Diance yu yibiao)
Aiming at the problem that the longitudinal current fault of distribution network lines affects the normal power supply, a zero-sequence compensation method of line longitudinal current differential protection based on 5G distribution network is proposed to improve the effect of current differential protection under different fault conditions. According to the characteristics of 5G distribution network, the differential protection architecture of distribution network is constructed. Combined with the principle of differential protection, the problem of line capacitive current in 5G distribution network under the two protection actions of no capacitive current compensation and capacitive current compensation is analyzed, and the action threshold under different protection actions is set to complete the zero-sequence compensation of longitudinal current differential protection. The experimental results show that the proposed method has good current differential zero-sequence compensation effect under different fault types. After compensation, the current differential change is small, the maximum amplitude of current fluctuation does not exceed 150 A, and the sensitivity of current differential protection is high. It can select appropriate differential protection action according to different faults.